Duas visões sobre o sujeito que transgride a norma penal: o direito penal do inimigo e a justiça restaurativa - (:unkn) unknown (Universidade Federal do Pampa, 2019)
This article aims in general to make a counterpoint between the Enemy's Criminal Law and the Restorative Justice, addressing the way which each one sees the subject that violates the criminal norm to finally understand if the imputed criminal as "enemy" is the same person that the Restorative Justice intends to restore. The methodology used was the bibliographic survey in academic productions in the format of books and articles. At the end of the critical analysis you can see that the imputed subject as the enemy is the same offender that the Restorative Justice tries to recover, so that both are differents forms to identify the criminal. For the enemy's criminal law, the criminal offender poses risks and should therefore be excluded from society. From the perspective of Restorative Justice, the treatment given to the violator of the penal norm allows us to conclude that he occupies the position of a person who can be restored and who is entitled to resocialization.
Keywords: Direito Penal; Justiça Restaurativa; Criminosos; Criminosos – Reabilitação; Criminal law; Restorative Justice; CNPQ::CIENCIAS SOCIAIS APLICADAS